Botany - G. De Graaff (Koedoe: African Protected Area Conservation and Science, 1987)
The National Botanic Gardens of the RSA aim to promote the conservation and research of the flora of southern Africa. Since 1944, some 13 publications were issued at regular intervals as supplementary volumes to the Journal of South African Botany. In 1984 the latter amalgamated with the South African Journal of Botany which is produced for both the National Botanic Gardens and the South African Association of Botanists. The numbering of volumes followed that of the Journal of South African Botany.